Peer influences in academic achievements and behaviours among students of Mara junior science college, Malaysia - Salleh, Mohamad Johdi (2011)
The study discusses the students’ perceptions of the peer influence in the academic achievements and behaviour among students of MARA Junior Science College Malaysia. The study involved 140 students of Forms Three, Four and Five who were purposely selected from the MARA Junior Science College in Pahang. The instruments used were survey questionnaire and the data was processed using the Statistical Package for Social Science (SPSS) version 15.0 for Windows. The findings show that the students have a clear definition of what and who are their peers and they are not influenced by their peers in decision making. They could relate peers to giving them a positive influence in terms of academic and are able to differentiate between the right and wrong act of their peers. The students clearly realized that a positive attitude should be attained to excel in academics. They have also agreed that those gifted and excellent students have an optimistic and positive affect towards their view and perspectives of learning. They are strongly influenced to be of the same level and status as their friends are. It is hope that the findings of this research would benefit teachers, educators, administrators, and, educational leaders to manipulate positively the peer influence in achieving good students in academics and moral attitudes.